2000
DOI: 10.1136/vr.147.18.517
|View full text |Cite
|
Sign up to set email alerts
|

Onion poisoning in a herd of dairy cattle

Abstract: Turpentine-induced inflammation in the chicken. A light-and electronmicroscope study, with emphasis on the macrophage, epithelioid cell, and multinucleated cell reaction. Avian Diseases 15, 533-550

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 1 publication
(2 reference statements)
1
13
1
Order By: Relevance
“…"content-markup(./ author-grp [1]/aff|./author-grp [1]/dept-list)> Hemolytic anemia caused by spontaneous ingestion of onion (Allium cepa) has been previously reported in cattle, sheep, dogs, cats, and horses. 1,3,7,8,10,14,15,18,25,27 Moreover, experimental disease also has been reported in sheep, dogs, and cats. [4][5][6]21,22 The epidemiology of onion toxicosis differs among species.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…"content-markup(./ author-grp [1]/aff|./author-grp [1]/dept-list)> Hemolytic anemia caused by spontaneous ingestion of onion (Allium cepa) has been previously reported in cattle, sheep, dogs, cats, and horses. 1,3,7,8,10,14,15,18,25,27 Moreover, experimental disease also has been reported in sheep, dogs, and cats. [4][5][6]21,22 The epidemiology of onion toxicosis differs among species.…”
mentioning
confidence: 99%
“…The epidemiologic characteristics are similar to those reported in others studies. 7,18,27 It has been shown that mortality rates may be high if onion consumption continues. The macroscopic and histologic lesions suggested a hemolytic-induced disease similar to that reported in spontaneous onion toxicosis in cattle, sheep, and horses.…”
mentioning
confidence: 99%
See 3 more Smart Citations